Where do remittances go? a comparative analysis on the inflows of remittance and the expenditure behavior of PH households during 2003 and 2021 - Aguila, Lian Diane L.; Cabatay, Hannah Jo Marie C.
The number of Overseas Filipino Workers (OFWs) has steadily increased since the 1950s. Remittances sent back to families at home have not only shielded the country from economic downturns but have also benefited households in financing their necessities. This study analyzes the relationship between remittances and household expenditure behavior during an almost two-decade period by looking at the effect of remittance in the expenditure share of the following items: food, food eaten at home, food eaten outside, health, education, occasion, recreation, and transportation and communication, using the FIES 2003 and 2021 dataset from the Philippine Statistics Authority. The Working-Leser Model was used wherein three (3) econometric techniques were performed to address endogeneity, heteroskedasticity, and the presence of zero values - Instrumental Variables Estimation using Two-Stage Least-Squares Regression, Quantile Regression, and Censored Tobit Analysis, respectively. All three techniques revealed consistent findings that remittances have positive significant effects on food eaten outside, health, and education expenditures, while there are negative significant effects on food and food eaten at home during both 2003 and 2021. The other expenditures show varying results in terms of sign and significance. Further, results show that there is stability in the expenditure behavior of households receiving remittances in terms of education, occasion, and recreation; that is, the effect of remittance is not significantly different in 2003 and 2021. This can be explained by the similar shocks during those years.